Optimizing Strategic Economic Pillars for National Resilience: A Study on the Impact of Trump’s 19% Tariff on Indonesia’s Economic Stability - Zahra, Khalista Arintyas; Kautsar, Farah Amilya; Ilma, Ajeng Faizah Nijma (Otoritas Jasa Keuangan, 2025)
As a global superpower, the United States plays a dominant role in international political and economic dynamics. The election of Donald Trump in 2017, under the “Make America Great Again” agenda, marked a shift toward protectionist trade policies, including higher import tariffs, in response to China’s rapid economic rise, triggering the U.S.–China trade war. Although U.S. import tariffs were subsequently reduced from 32% to 19%, they continued to pose risks to economic stability in developing countries, including Indonesia. This study employs a mixed-methods approach combining qualitative analysis and quantitative tools—SWOT, Internal–External Factor Evaluation (IFE–EFE), and the Analytic Hierarchy Process (AHP) to examine the impact of the trade war on Indonesia’s economic stability and to formulate a prioritized strategic policy mix. The results indicate that strengthening national economic resilience requires a balanced inward- and outward-looking strategy, including export-oriented industrial downstreaming supported by TKBI policies, export market diversification through RCEP and IEU–CEPA partnerships, enhanced utilization of domestic products (P3DN), and the implementation of Local Currency Settlement (LCS). The findings suggest that enhancing economic resilience in developing countries facing protectionist trade shocks requires a coordinated policy mix integrating trade, industrial, monetary, and financial stability policies, while highlighting the strategic role of financial authorities in mitigating transmission risks from global trade disruptions to the domestic financial system.